Creating an Enabling Environment - UNCTAD; World Bank (World Bank, Washington, DC, 2018)
This note provides guidance on how to create an investment climate that is conducive to attracting high-quality, responsible investment in agriculture. The investment climate needs to enable investors to survive, to thrive, and to contribute to the local community and the broader economy in a socially and environmentally responsible way. Investors in the agriculture sector noted a variety of factors that inhibit their ability to run successful operations. Failed or struggling investments have consequences that extend well beyond the financial losses that investors incur. An effective enabling environment contributes to the chances of investor success, which is in the interests of all stakeholders.